آں حضورﷺ کے غزوات وسرایا کی معاشی جہات (Al-Qamar, 2022)
Allah has entrusted some requirements to man, one of them is the necessity of livelihood. This requirement is very important to sustain life. There is an abundance of livelihood resources in the universe for every human being. Allah Almighty has created the means of providing them. Access and distribution of these resources is the responsibility of man. Lack of livelihood resources is not the main cause of economic oppression and injustice, but unfair and wrong distribution of these resources is the real reason. Then man comes to war to maintain control over these resources. Wars were fought to capture the resources of other nations and peoples. And this tradition has existed in every age and time and among the followers of every religion. The concept of booty after the end and victory of war and jihad is not only in Islam, but there are evidences of it in Bani Israel and other nations as well. It was not maintained for the possession of resources or resources, but it was allowed to achieve higher objectives such as establishing peace and ending sedition. Invasions and raids occurred at different times of the Prophet's covenant. Their effects have different dimensions and among them, the most important and prominent dimension is related to livelihood. In this discussion, the economic aspects of Ghazwāt and Sarāyā will be reviewed.
Keywords: Economic Oppression; Invasions; Economic aspects; Ghazwāt; Sarāyā